Arte e aparato para gravação e reprodução de sons ou sinais do final do século XIX e início do XX: da gravação mecânica à gravação eletromagnética - Braga, Rodrigo Trevisan (2021)
The technology to record and reproduce sounds and signals was developed in the late 19th and early 20th centuries based on research on the acoustic phenomenon, tuning, timbre and electromagnetism. Two forms of recording were presented, one mechanical and the other electromagnetic. Hermann Ludwig Ferdinand von Helmholtz's research (1821-1894), as well as the sound measurement apparatus created by Karl Rudolph Koenig (1832-1901), had a strong influence on the development of two forms of mechanical recording: the Phonograph, patented by Thomas Edison (1847-1931), and The Gramophone, by Emil Berliner (1851- 1929). The form of electromagnetic recording was initially proposed by Oberlin Smith (1840- 1926), who theoretically presented a way to record sounds and signals that would be of better quality than the mechanical format. However, this theory was only put into practice by Valdemar Poulsen (1869-1942) when presenting his Telegraphone, with a method of recording sounds and signals that could be part of the telephony circuit, which can be used both to record messages and to reproduce previously recorded messages. The present thesis sought to identify the theoretical foundations, experiences and apparatus that made possible the progress in the creation of sound recorders and reproducers, thus being able to point out the importance of several scientific research, with emphasis on the research on Helmholtz's acoustics and the research on electromagnetism by James Clerk Maxwell (1831-1879)